ANALYSIS OF QUALITY OF LIFE IN CAREGIVERS AFTER AQUATIC PHYSIOTERAPY. (Fiep Bulletin - online, 2011)
The caregiver is who assumes the responsibility of the care, support or assist the need of the person cared for, to better health. The lack of self-care disability affects of the quality of life, for this is necessary to be well and enjoy life. The progress of studies on the therapeutic benefits in an aquatic enviroment has been increasingly developed. The aquatic phisioterapy has its main purpose providing an improvement in function and quality of life. The purpose of the study is analyze responses related of quality of life in caregiver after aquatic phisioterapy. Five mothers of neurological patients participated in the study, for evaluation the quality of life we used the SF-36 questionnaire before and after treatment. The attendances were held in the hydrotherapy sector, in rehabilitation center from Assis Gurgacz college - FAG. In the period from February to July, totaling 20 meetings. The results were presented through graphs and calculation of simple percentages. Using the SF - 36 questionnaire of quality of life before and after treatment has showed the favorable response on quality of life of caregivers, especially in items of functional capacity, limits of physical and mental health. Indeed, they become necessary programs of support aimed to caregivers, such as preventive and therapeutic action, within institutions, to provide an incentive to improve the quality of life.
Keywords: Caregivers; Aquatic phisioterapy; Quality of life